Estrategias metodológicas en la conducta disruptiva de los niños de cuarto grado A de la Escuela de Educación Básica Mons. Juan María Riofrío de la ciudad de Loja, período académico 2018- 2019. Lineamientos alternativos - Sarango Robles, Silvia de Jesus (2019)
The present research called Methodological Strategies in the Disruptive Behavior of Fourth Grade A Children of the School of Basic Education Mons. Juan María Riofrío of the city of Loja, academic period 2018-2019. Alternative guidelines, has as a central problem: How do the methodological strategies influence the disruptive behavior of fourth grade students A of the School of Basic Education Mons. Juan María Riofrío of the city of Loja, period 2018-2019 ?, the same which has as a general objective: To diagnose methodological strategies in the disruptive behavior of fourth grade children A of the School of Basic Education Mons. Juan María Riofrío of the city of Loja, academic period 2018-2019. The type of study used is descriptive; its design is not experimental; The methods used were the scientific, inductive, deductive, descriptive, analytical, synthetic, hermeneutic and statistical model; information gathering techniques: observation, interview and survey; instruments: questionnaire, observation guide; procedure for diagnosis, theoretical basis, alternative guidelines approach; As a result, the existence of disruptive behaviors was verified and that the application of methodological strategies is not adequate, which has resulted in the teaching-learning process not developing normally and also children with this difficulty are not integrated into the process. 19 students and three teachers participated in the research work. It is concluded that the application of methodological strategies in disruptive behavior during the teaching-learning process is an essential part of actively integrating children with this difficulty into the educational process allowing the teacher to intervene properly and thus achieving that the educational task is developed in a harmonious environment of respect, responsibility and understanding.